Protocol of the Swiss Longitudinal Cohort Study (SWICOS) in rural Switzerland. Issue 11 (28th November 2016) - Schoenenberger, Andreas W; Muggli, Franco; Parati, Gianfranco; Gallino, Augusto; Ehret, Georg; Suter, Paolo M; Schoenenberger-Berzins, Renate; Resink, Therese J; Erne, Paul
Abstract : Introduction: Increased longevity and consequent major changes in demographics and population lifestyles necessitate new approaches to reduce the burden of ageing-related diseases (including cardiovascular disease) and maintain an optimal quality of life. This study aims to examine and longitudinally follow health status and disease risk factors in a Swiss rural cohort, evaluating all health-related research and practice disciplines to assure development of new implementable and successful preventive strategies for healthy ageing. Methods and objectives: Small Swiss villages with low migration rates will be selected for this study. 2 villages (Cama/Lostallo) have already been selected as initial study sites. All residents (age ≥6 years, no upper age limit) are eligible. The target enrolment number per village is 300. Examinations and measurements encompass medical history, anthropometry, cardiac and vascular health, pulmonary function, physical performance, nutritional, mental and emotional status, biochemical and molecular analyses. Follow-up examinations (identical to baseline) will be performed after 5 and 10 years, and in 10-year intervals thereafter. The major objective is to assess, and observe change in, health status over time in a prospective manner. Secondary objectives are to: (1) identify 'hidden' (asymptomatic and/or unrecognised) health problems which enhance risk for chronic diseases; (2) identify barriers to accessing healthcare and adapting health behaviours; (3) evaluate efficacy of present preventive strategies and recommendations; (4) evaluate knowledge and attitude towards ongoing health programmes and public health recommendations; (5) monitor change and progress towards the national health objectives; (6) formulate new preventive strategies and recommendations based on the findings and knowledge base of the past 10 years; (7) formulate models for successful prevention of chronic diseases and for healthy ageing. Ethics and dissemination: The Ethics Committee of Nordwest-und Zentralschweiz approved this study (EKNZ 2014-209). It is registered at ClinicalTrials.gov (NCT02282748 ). Findings will be disseminated through scientific articles/presentations and public events.